Regulation of Group Company Expansion Restrictions in the Coal Mining Sector Viewed from Indonesian Laws and Regulations - Hartana, Hartana (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
The growth of coal mining business in the last ten years in The Indoensia region must certainly be balanced with the fulfillment of the prevailing laws and regulations. So in this article will be discussed about the legislation that specifically regulates the restriction of expansion of group companies, especially in the coal mining sector in Indonesia. The result of this study is Law No. 4 of 2009 on Mineral and Coal Mining provides restriction arrangements for group companies, namely IUP or IUPK holders are prohibited from involving subsidiaries and/or affiliates in the field of mining services in the mining business area they are working in, except with the permission of the Minister. The maximum area ownership of IUP in group companies is not limited.